DOI: 10.32657/10356/68926
|View full text |Cite
|
Sign up to set email alerts
|

Selective laser melting of novel titanium-tantalum alloy as orthopaedic biomaterial

Abstract: Selective laser melting (SLM) is an additive manufacturing (AM) technique that is capable of fabricating complex functional three-dimensional (3D) metal parts of high relative density with the complete melting and fusion of powders. As a powder bed fusion technology, SLM has the potential in expanding the materials library by formation of alloys that were previously difficult to achieve from metal powder mixtures that can be customised according to the application requirements. Titanium-tantalum (TiTa) is a po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 136 publications
0
5
0
1
Order By: Relevance
“…Different orthopedic implants are typical applications of these powdered metals for 3D printing. Since many bone tissues in the human body have varying porosity, 3D uneven structures from macro-to nanoscale, and differing mechanical strength from the outer to the inner section [20,53], orthopedic implants not only need to match this functionally graded structure [54], but also feature sufficient toughness, strength, tribology, biocompatibility, and wear resistance between artificial joints [53,55], which often require significant geometric optimization and surface modification [56]. These criteria are challenging to fulfill for the structure and materials of orthopedic implants and make it difficult to realize through traditional manufacturing methods.…”
Section: Raw Materials Quality Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…Different orthopedic implants are typical applications of these powdered metals for 3D printing. Since many bone tissues in the human body have varying porosity, 3D uneven structures from macro-to nanoscale, and differing mechanical strength from the outer to the inner section [20,53], orthopedic implants not only need to match this functionally graded structure [54], but also feature sufficient toughness, strength, tribology, biocompatibility, and wear resistance between artificial joints [53,55], which often require significant geometric optimization and surface modification [56]. These criteria are challenging to fulfill for the structure and materials of orthopedic implants and make it difficult to realize through traditional manufacturing methods.…”
Section: Raw Materials Quality Controlmentioning
confidence: 99%
“…These criteria are challenging to fulfill for the structure and materials of orthopedic implants and make it difficult to realize through traditional manufacturing methods. Titanium alloy and tantalum are well-known for their beneficial mechanical properties, corrosion resistance, and biocompatibility [53,57]. With the support of 3D printing technology, these powdered metals can well manufacture implants that meet the requirements and are more conducive to osseointegration.…”
Section: Raw Materials Quality Controlmentioning
confidence: 99%
“…Um exemplo na área aeroespacial da otimização em componentes estão as turbinas com alívio de peso. Na área médica, se destacam a fabricação de implantes ortopédicos personalizados e com estruturas do tipo lattice, proporcionando redução de peso, diminuindo procedimentos cirurgicos ao longo do tempo e promovendo maior aceitação com os tecidos (SING, 2019).…”
Section: Vantagens E Limitações Dos Processos De Maunclassified
“…Limited literature is available on Ti-Ta alloys manufactured with SLM. Sing et al [32,33,35] have reported the effect of SLM parameters on part quality and mechanical properties for a dense Ti-50Ta alloy (50 wt.% of each element). Despite difficulties in fully melting the tantalum particles, they reported high densification and good mechanical properties compared to cp-Ti and Ti-6Al-4V parts, with dimensional accuracy and mechanical properties affected by printing parameter control (eg.…”
Section: Introductionmentioning
confidence: 99%